Assessment of Seminal Plasma Creatine Kinase Activity and Malondialdehyde Concentration among Normozoospermia but Infertile Men (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Despite the considerable research efforts that have been made by Reproductive Biologists to understand the etiologies of male infertility, idiopathic male factor infertility still remains unexplained. It occurs in about 10% cases of infertility. Since the etiologies cannot be identified using routine semen analysis, it is important to identify cellular and sub-cellular sperm complications that may help to explain the cause(s) of the infertility, thus stimulate caregivers to direct the further work-up, diagnosis and counseling of affected individuals. The objective of this study was to determine seminal plasma creatine kinase (CK) activity and malondialdehyde (MDA) concentration among normozoospermia but infertile males. Materials and Methods: After routine semen analysis, seminal plasma CK activity and MDA were determined among 75 normozoospermia but infertile men and 50 men of proven fertility using spectrophotometric method. Unpaired Students-t-test and regression analysis were used to compare and associate CK activity and MDA concentration with sperm characteristics. Results: Significantly higher (p